2015
DOI: 10.3390/su71014344
|View full text |Cite
|
Sign up to set email alerts
|

The Sustainability and Challenges of Business Incubators in the Western Cape Province, South Africa

Abstract: Abstract:Notwithstanding the growing interest in business incubation programmes and the benefits derived from such programmes, the path is beset by numerous challenges. This paper investigates the challenges faced by business incubators (BIs) as they strive to support their clients. The study utilized a qualitative approach to collect data by way of interviews to gain in-depth knowledge and understanding of the concept and challenges of business incubators. The data were collected using structured and unstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(83 citation statements)
references
References 25 publications
3
77
0
3
Order By: Relevance
“…The findings of this study also indicated that lack of entrepreneurial skills is a challenge to the growth of business incubatees. Entrepreneurial skills include creativity, innovation, risk-taking and ability to interpret successful entrepreneurial role models and identification of opportunities (Fatoki, 2012; Lose & Tengeh, 2015). The results of this research paper are in consistence with literature.…”
Section: Presentation and Discussion Of Findingssupporting
confidence: 69%
See 1 more Smart Citation
“…The findings of this study also indicated that lack of entrepreneurial skills is a challenge to the growth of business incubatees. Entrepreneurial skills include creativity, innovation, risk-taking and ability to interpret successful entrepreneurial role models and identification of opportunities (Fatoki, 2012; Lose & Tengeh, 2015). The results of this research paper are in consistence with literature.…”
Section: Presentation and Discussion Of Findingssupporting
confidence: 69%
“…Focusing on incubator service and sustainability have been Cullen, Calitz and Chandler (2014), Dubihlela and Van Schaikwyk (2014). A close parallel has been that of Lose and Tengeh (2015) that looked at the challenges of business incubators in the Western Cape.…”
mentioning
confidence: 99%
“…Respondents thus tended to agree that lack of education and training is a challenge facing women entrepreneurs in Kigali. Lose and Tengeh [27] believe that success in business relies on training, education and experience. The statement which suggested that the lack of a support network was a challenge facing women entrepreneurs in Kigali obtained a mean value of 3.64, slightly above the neutral mean of 3.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Education, skills and the experience in industry with which an entrepreneur starts a business influence its chances of success [27]. It has also been suggested that networks facilitating the flow of information from various sources could be a key factor in the success of women's entrepreneurial ventures [28].…”
Section: Challenges Women Entrepreneurs Face In Doing Business In Kigalimentioning
confidence: 99%
“…The B-Schools help in increasing knowledge base, by identifying opportunities, and by pointing out ways to overcome barriers imposed by ones environment. Lose and Tengeh [17] study included limited research participants to the business incubators on the database of a local organization that promotes small and medium enterprises (SMEs) development strategy and programmes in the Western Cape Province. All five business incubators on the database were deemed suitable for the study.…”
Section: Literature Review Business Incubationmentioning
confidence: 99%